The impact of maturing food safety culture and a pathway to economic gain. (April 2019) - Jespersen, Lone; Butts, John; Holler, Greg; Taylor, Jeff; Harlan, Dave; Griffiths, Mansel; Wallace, Carol A.
Abstract: Research into the connection between organizational effectiveness and culture has been documented since the early nineteen nineties. A connection between economic performance and organizational culture has been established directly linking strong cultural drivers to economic performance in both the finance and retail sectors. This research proposes a similar association between food safety culture, the measures of maturity and cost of poor quality. Through data collected at five multi-national food companies, this association is explored, and an improved food safety maturity model suggested. The authors also propose a dynamic model of food safety culture, segmenting it into 4 building blocks: I. Organizational effectiveness, II. Organizational culture norms, III. Working group learned and shared assumptions, and behaviours, and IV. Individual intent and behaviours; and discuss the crucial role of actions between building blocks as part of the pathway to realizing economic gain. Highlights: Explores organizational culture, effectiveness, and performance in the food industry. Demonstrates theoretical economic gain from building food safety culture maturity. Refines and strengthens a food safety culture maturity model for practical application. Proposes a dynamic model of food safety culture building block and interactions. Empirical study of culture performance within five global food manufacturing companies.